Selection of FUV auroral imagers for satellite missions. Issue 10 (15th October 2016) - Unick, Craig; Donovan, Eric; Spanswick, Emma; Uritsky, Vadim
Abstract: A survey of previously flown and recently designed FUV auroral imagers is presented in conjunction with selection criteria to optimize the potential scientific impact of future satellite‐based FUV auroral observations. The selection of the appropriate suppressive imager is ultimately broken down to four field‐of‐view categories: (1) less than 10°, (2) 10° to 16°, (3) 16° to 24°, and (4) greater than 24°. The determination of the field of view follows as a necessary consequence of the orbit of the satellite, which is often imposed by the mission. The first category of imagers has a wide range of available choices, the second and third categories have a couple of options each where a distinction is made between narrow and wide aggregate filter bandwidth, and the fourth category is limited to on‐axis designs introduced by the authors. High‐resolution imaging is possible up to 50° field of view with the class of imager design first presented in this paper. Key Points: Selection criteria have been suggested for choosing FUV auroral imagers for satellite missions New FUV auroral imager performance is compared to previously flown imagers A variety of new potential imager designs are described